(untitled) (Research, Society and Development, 2021)
An integrating review of the literature about the perspectives of the pharmaceutical practices in Adrenal Insufficiency (AI) was carried out. Researches were done on the LILACS database, Medline (Pubmed), and Scientific Electronic Library OnLine-SCIELO. Articles published between January 2007 and February 2021, written in Portuguese, English, and Spanish, were included. A total of 43 articles were selected to compose the review. A great deal of the studies considers patient education fundamental for the treatment and AI control. Among the education measures found in these studies, which can subside the service routines are: guidelines on the precipitating factors, signs and disease symptoms, dose adjustment, drug interaction, and condition identification cards. Relevant interventions of clinic management reported hospital discharge plans, management of AI acute and chronic phases, home care management, and routine outpatient follow-up. For an effective self-care support system, patient-centered assistance must be the core of the health care standards model. The review establishes that the AI patient follow-up must be performed regularly by a multidisciplinary team. It also allowed the identification of health measures that a pharmacist integrated with the healthcare team should perform.